Assessment of learning outcomes and analytical sheet in Arabic language activities for the fifth year of primary education - mekkaoui, khadidja (El Omda in Linguistics and Discourse Analysis, 2024)
The Ministry of Education in Algeria paid great and distinct attention to the fifth year of primary education, so it implemented a new evaluation strategy during the 2022/2023 academic season, known as the “acquisitions assessment exam,” which is subject to standards and assessments, which it interprets and controls. Given the novelty of the topic, this article came to shed light on the concept of evaluating gains in the Algerian school, and how to apply it in the classroom, through a descriptive and analytical study to demonstrate its importance and the newness it brings.